A SIMPLE REVERSE PHASE-HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY METHOD DEVELOPMENT AND VALIDATION OF VALSARTAN IN BULK AND IT’S TABLET DOSAGE FORM - Godela, Ramreddy; Bhavani, Sherisha (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The most important objective of the present research work is to develop simple, specific, rapid, accurate, and sensitive reverse-phase high-performance liquid chromatography method and validated for the qualitative and quantitative determination of valsartan in its active pharmaceutical ingredient and tablet dosage form according to ICH guidelines. Proposed Method: An isocratic separation was done using Phenomenex C18 column possess 75Ã—4.6 mm, 2.6 Î¼,100 A0 dimensions with mobile phase composition of water:acetonitrile (30:70% v/v) by maintaining 1 ml/minute flow rate and response detected at a wavelength of 247 nm. Results: The retention time of valsartan was found to be 2.71 minutes, limit of detection and limit of quantification were observed at 1.24 Î¼g/ml and 3.6 Î¼g/ml concentration, respectively, and a calibration curve was linear in the concentration range of 5-50 Î¼g/ml with coefficient of correlation 0.99. The percentage recovery (accuracy) was in the range of 98.9-102%, and the % relative standard deviation was observed to be <2%. Conclusion: The proposed method was validated for accuracy, precision, sensitivity, linearity, and robustness and successfully employed for the quantitative determination of valsartan in tablet dosage form in quality control department of pharmaceutical industry.